Brainstem astrocytoma as a neuro-Behçet's disease mimic. Issue 1 (7th December 2018) - Manasson, Julia; Howard, Jonathan; Nowatzky, Johannes
Abstract : A 58-year-old man with a history of recurrent aphthous ulcers since childhood was admitted to the hospital with acute neurological decline characterised by loss of motor dexterity, dysarthria, dysphagia and unsteady gait. MRI brain was significant for symmetrical hyperintense T2 fluid attenuated inversion recovery (FLAIR) in the corticospinal tracts, including parts of the pons and the mesodiencephalic junction. Though initial concern was for neuro-Behçet's disease, brain biopsy ultimately revealed a diagnosis of astrocytoma. This report demonstrates a mimic of neuro-Behçet's disease and the importance of confirming the correct diagnosis prior to initiating therapy.